2017
DOI: 10.1590/1676-0611-bn-2016-0294
|View full text |Cite
|
Sign up to set email alerts
|

Influence of landscape structure on Euglossini composition in open vegetation environments

Abstract: Abstract:The fauna of Euglossini bees is poorly known in savanna regions, making it difficult to understand how these bees use open vegetation environments. The aim of this study was to evaluate the influence of landscape structure on species abundance and composition of Euglossini bees in naturally heterogeneous savanna landscapes. Nine sites were sampled monthly using six traps with chemical baits. Three aromatic essences (eucalyptol, methyl salicylate and vanillin) were used to attract the Euglossini. Surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…On the other hand, eight recent studies do show empirical support for the habitat amount hypothesis. A study in the naturally heterogeneous savanna landscape of the Chapada Diamantina in Brazil did so for Euglossini bees (Moreira et al., ), a study within five major industrial sites in Europe did so for five out of seven tested taxa (Piano et al., ), while a study on fluvial islands in Amazonia did so for arboreal mammals (Rabelo, Bicca‐Marques, Aragón, & Nelson, ). Both patch size and habitat amount in the local landscape independently affected species numbers of saproxylic beetles in German forests, without an interaction effect, hence consistent with the habitat amount hypothesis and refuting the island effect (Seibold et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, eight recent studies do show empirical support for the habitat amount hypothesis. A study in the naturally heterogeneous savanna landscape of the Chapada Diamantina in Brazil did so for Euglossini bees (Moreira et al., ), a study within five major industrial sites in Europe did so for five out of seven tested taxa (Piano et al., ), while a study on fluvial islands in Amazonia did so for arboreal mammals (Rabelo, Bicca‐Marques, Aragón, & Nelson, ). Both patch size and habitat amount in the local landscape independently affected species numbers of saproxylic beetles in German forests, without an interaction effect, hence consistent with the habitat amount hypothesis and refuting the island effect (Seibold et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Some these studies have shown structural differences in euglossine bee communities from distinct biogeographical regions, and differences have usually been attributed mainly to historical factors (Aguiar et al 2014). However, comparative studies of orchid bee communities from different vegetation physiognomies have shown that regional differences in community structure are also influenced by climatic, geomorphological, and/or vegetational parameters (Nemésio & Silveira, 2007;Sydney et al, 2010;Mattozo et al, 2011;Aguiar et al, 2014;Nemésio & Vasconcelos, 2013;Giangarelli et al, 2015;Costa & Francoy, 2017;Medeiros et al, 2017;Moreira et al, 2017).…”
mentioning
confidence: 99%
“…However, there are still theoretical controversy and few empirical data regarding the effects of the loss of natural environments on network characteristics such as nestedness (the extent to which interactions with specialist species are a subset of interactions with generalist species) and complementary specialization-Hʹ 2 (the extent to which specialist species interact with other specialists) (Blüthgen and Klein 2011;Weiner et al 2014). Few empirical studies have actually investigated the effects of deforestation on the structure of plant-pollinator networks, with even fewer information available in tropical regions (Hagen and Kraemer 2010;Gómez et al 2011;Ferreira et al 2013;Dáttilo et al 2015;Moreira et al 2015Moreira et al , 2017. The existing network studies show a positive influence of increasing cover of natural vegetation, particularly when the landscape heterogeneity is high (Moreira et al 2015;Boscolo et al 2017;Moreira et al 2017).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Ecological networks of biotic interactions provide an efficient approach to understand the complex set of connections among several species when simultaneously influenced by many different factors (Bascompte et al 2003). The study of mutualistic interaction networks, such as plant-pollinators, may improve the ecological knowledge beyond species diversity studies to assess the impacts of habitat change on biodiversity and ecological processes functioning (Forup and Memmott 2005;Sabatino et al 2010;Ferreira et al 2013;Moreira et al 2015Moreira et al , 2017. Those studies can provide more complete guidance for conservation of biodiversity, ecological processes, and natural environments.…”
Section: Introductionmentioning
confidence: 99%